2013
DOI: 10.1016/j.jpsychires.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of posttraumatic stress symptomatology in older persons affected by a large-magnitude disaster

Abstract: This study examined the nature and determinants of longitudinal trajectories of disaster-related posttraumatic stress disorder (PTSD) symptoms in older persons affected by a large-magnitude disaster. Two hundred six adults age 60 or older (mean=69, range=60–92) who resided in the Galveston Bay area when Hurricane Ike struck in September 2008 completed telephone interviews an average of 3-, 6-, and 15-months after this disaster. Latent growth mixture modeling was employed to identify predominant trajectories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 63 publications
3
75
0
2
Order By: Relevance
“…These findings are consistent with other disaster research that has reported financial problems after a disaster were associated with a chronic PTSD trajectory. (Pietrzak et al, 2013) Indeed, these data suggest that not all stressful life events exert a similar effect on mental health. Therefore, a stress management program may offer greater impact if oriented on those stressful life events that have the largest effect on mental health.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with other disaster research that has reported financial problems after a disaster were associated with a chronic PTSD trajectory. (Pietrzak et al, 2013) Indeed, these data suggest that not all stressful life events exert a similar effect on mental health. Therefore, a stress management program may offer greater impact if oriented on those stressful life events that have the largest effect on mental health.…”
Section: Discussionmentioning
confidence: 93%
“…(Brewin et al, 2000;Luszczynska et al, 2009) Indeed, stressful life events post-trauma exposure are often related to poorer mental health, including PTSD. (Brewin et al, 2000;Bonanno, 2012;Solomon et al, 1989) For example, Pietrzak and colleagues (Pietrzak et al, 2013) found that greater number of traumatic and stressful life events after Hurricane Ike, particularly financial problems, were associated with a chronic PTSD trajectory. Thus, past work indicates that not all stressful life events necessarily exert a similar effect on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is equally possible that PTSS trajectories have varied across studies because of differences in the source population under study. Studies documenting PTSS trajectories have included studies of: traumatic injury survivors (Bryant et al, 2015; deRoon-Cassini, Mancini, Rusch, & Bonanno, 2010), rape victims (Armour, Shevlin, Elklit, & Mroczek, 2012; Steenkamp, Dickstein, Salters-Pedneault, Hofmann, & Litz, 2012), mass trauma victims (Norris et al, 2009; Pietrzak et al, 2014; Pietrzak, Van Ness, Fried, Galea, & Norris, 2013; Van Loey, van de Schoot, & Faber, 2012), or deployed service members (Bonanno et al, 2012; Sampson et al, 2015). As each of these populations exhibits a different distribution of risk factors and traumatic event experiences, it is possible that these differences induce the heterogeneity of PTSS trajectories that has been observed among PTSS studies.…”
mentioning
confidence: 99%
“…8 What is distinctive about the Australian study 1 is its comprehensive and precise information on posttraumatic trajectories, with respect both to non-PTSD outcomes and, perhaps most interestingly, to the high level of migration across diagnostic classes as assessed at 3, 12, and 72 months.…”
Section: E1154mentioning
confidence: 99%